POTENSI ANTIBAKTERI EKSTRAK ETANOL JAMUR KANCING (Agaricus bisporus) SEBAGAI ANTIBAKTERI - Siska Nuryanti; Fitriana Fitriana (Jurnal Fitofarmaka Indonesia, 2018)
A research had been done on antibacterial activity of extract and the aim was to determine the antibacterial activity and inhibitory potency. The research was started by screening test using Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, Salmonella typhi, Staphylococcus epidermidis, Shigella dysenteriae, Staphylococcus aureus, Streptococcus mutans and Vibrio cholerae. Results showed that the Agaricus bisporus ekstract inhibited Bacillus subtilis, Shigella dysenteriae, Staphylococcus aureus, and Vibrio cholera at concentrations 0,1% and 1%. The results obtained Minimum Inhibitory Concentration (MIC) Agaricus bisporus extract against at concentrations of 0,1%. In the Minimum Bactericidal Concentration (MBC) test Agaricus bisporus extract against at concentrations of 0,8%. Agaricus bisporus extract has antibacterial activity wich was indicated by the inhibitory zone diameter. The biggest inhibitory zone diameter of Agaricus bisporus contained in bacteria Bacillus subtilis on the concentration of 6.4% (13 mm)